HISTORICAL IDENTIFICATION IN CULTURAL HERITAGE BUILDING LICENSES ONKAUMAN GREAT MOSQUE KEBUMEN 1838 AD - Lian Salimatuzzulfa; Ita Dwijayanti (2024)
Indonesia is the second country in the world which has 84.35% Muslim population of its total population. Moreover, in Java, almost every region has a Muslim village with the name Kauman. Kauman is synonymous with a mini santri city which is characterized by a community that carries out activities at the mosque, many people then call it the Kauman Mosque. The Kauman Mosque in each region has its own uniqueness and characteristics, one of which is in Kebumen. Kauman Kebumen Great Mosque is the largest mosque in Kebumen Regency, Central Java. This mosque was founded by KH Imanadi in 1838 AD. With almost 2 centuries of age, it is said that this mosque has not been included in the list of cultural heritage buildings. In general, the Great Mosque in several locations (for example in Solo or Yogyakarta) has a burial complex in the western part of the mosque, but this is different from the Kauman Great Mosque in Kebumen, where no traces of graves have been found. The founders of the mosque or religious figures were not buried in the mosque area. The Great Kauman Mosque in Kebumen has undergone several renovations, but during these renovations, it is said that it still maintained traditional Javanese architecture with similarities to the typology of the Great Mosque of Demak. This is what attracted researchers to identify and analyze the history, cultural acculturation and forms of architectural change at the Kauman Great Mosque, Kebumen. This research uses a qualitative historical approach method through stagesheuristics (data collection by means of interviews with related parties and also collecting sources of oral history of the Kauman Kebumen community and also takmir mosques), verification (source criticism, this is done by limiting research observations so that the focus is on the objectives of this research), interpretation (analysis is carried out by creating a structured narrative that can be accounted for in its truth and novelty), and historiography (carried out to convey the results of observations in three chapter discussions which will be completed in approximately 2-6 months). The results of the research are to find out the history of the Great Kauman Mosque, Kebumen, cultural acculturation which can be seen from the acculturation of Islamic and Hindu culture in the mosque building and the factors that cause this almost 2 century old building to not be included in the cultural heritage building in 2023. The reasons why the building renovation was influenced environmental factors, namely socio-cultural, religious, economic, political and legal that apply at a certain time. There have been renovations several times, but there are parts that are maintained and preserved in order to preserve historical evidence in the form of archaeological objects in the form of artifacts and features to convey information that has been passed down from generation to generation in an effort to maintain the existence of the glory of the past.